The Bromeliad Blue Horn Katydid—a new genus of the Cone-headed Katydid (Orthoptera: Tettigoniidae: Conocephalinae: Copiphorini) from the Serra da Jibóia, Bahia, Brazil - de Mello Mendes, Diego Matheus; Da Silva Neto, Alberto Moreira (Zootaxa, 2022)
The tribe Copiphorini (Conocephalinae: Tettigoniidae) currently comprises 58 genera and 442 species widely distributed across all continents, with the exception of Antarctica. In Brazil, 19 genera and 100 species are recorded. The tribe stands out within the Conocephalinae for including several genera with the fastigium-vertex expanded, forming horns and other elaborate structures. In this work, the new monotypic genus Ibityraboia gen. nov. and the new species Ibityraboia caraguata sp. nov., from Serra da Jibóia, located in the Agreste of Bahia, Brazil. Maps, natural history observations, and comments on the differences between Ibityraboia gen. nov. and Copiphora Serville are provided.